Exploration of an ice-cliff grounding zone in Antarctica reveals frozen-on meltwater and high productivity - Owsianowski, Nils; Richter, Claudio; Alfred-Wegener-Institut Helmholtz Zentrum für Polar- und Meeresforschung, Bremerhaven, Germany; Universität Bremen, Bremen, Germany (Communications Earth & Environment, 2021)
Ice fluxes across the grounding zone affect global ice-sheet mass loss and sea level rise. Although recent changes in ice fluxes are well constrained by remote sensing, future projections remain uncertain, because key environments affecting ice-sheet dynamics – the ice-sheet bed and grounding zone – are largely unknown. Here, we used a remotely operated vehicle to explore the grounding zone of a Weddell Sea tidewater ice cliff. At 148 m we found a 0.3–0.5 m gap between the ice and the seafloor and a 0.4 m clear facies of debris- and bubble-free basal ice, suggesting freeze-on of meltwater in the distal marine portion of the ice sheet over the last 400 yr. Ploughmarks and low epifauna cover reveal recent grounding line retreat, as corroborated by satellite remote sensing. We found dense algal tufts on the ice cliff and high phytoplankton pigment concentrations, suggesting high productivity fuelled by nutrients from ice melt. As grounded tidewater ice cliffs rim 38% of the Antarctic continent, sinking and downwelling of organic matter along with low benthic turnover may contribute to enhanced carbon sequestration, providing a potentially important feedback to climate. Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (Alfred-Wegener- Institute, Helmholtz Centre for Polar and Marine Research) https://doi.org/10.13039/501100003207 https://doi.org/10.1594/PANGAEA.909526 https://doi.org/10.1594/PANGAEA.924822